P469 Spontaneous resolution to negative and non-viable status of vaginal and rectal Chlamydia trachomatis infection (FemCure). (14th July 2019) - Dukers-Muijrers, Nicole; Janssen, Kevin; Götz, Hannelore; Loeff, Maarten Schim Van Der; Bruisten, Sylvia; Vries, Henry De; Hoebe, Christian; Wolffs, Petra
Abstract : Background: Spontaneous resolution (clearance) of Chlamydia trachomatis (CT) infections can occur between diagnosis by nucleic acid amplification assays (NAAT) and treatment. Moreover, viability polymerase chain reaction (V-PCR) techniques showed that part of non-resolved NAAT positives represent non-viable CT. This may impact clinic policies aiming to restrict antibiotic treatment (i.e. to viable CT only). We followed 560 CT diagnosed women to assess the proportion without viable CT at follow-up, and associated risk factors. Methods: Vaginal (vCT) or rectal (rCT) NAAT positive adult women, negative for HIV, syphilis and Neisseria gonorrhoeae, who not recently used antibiotics, were included at three STI outpatient-clinics (Netherlands, 2016–2017; FemCure). At clinic-diagnosis women were (a) vCT positive, rCT untested (n=351), (b) vCT, rCT positive (n=155), (c) vCT positive, rCT negative (n=25), (d) vCT negative, rCT positive (n=29). After a median of 8 [IQR:7–12] days, before treatment, samples were tested using NAAT and V-PCR. We present percentages of women without viable CT at follow-up, and tested which factors (group [a-d], age, education, non-western-background, symptoms, anal/vaginal sex, sexpartners) were associated, using logistic regression. Results: At follow-up, percentages of women NAAT negative at both anatomic sites were 5.4% (a), 0.6% (b), 32.0% (c), and 27.6% (d). Percentages of women without viable CT (i.e. NAAT negative or NAAT positive and V-PCR undetectable) at both anatomic sites were 9.4% (33/351, a), 3.9% (6/155, b), 52.0% (13/25, c), and 41.4% (12/29, d). Alongside group (p<0.001), older age was independently associated (odds ratio: 1.07 per year (95%CI: 1.01–1.13; p=0.029) with lack of viable CT. Conclusion: Less than ten percent of STI-clinic women diagnosed with vaginal and rectal CT (or were rectally untested) did not have viable CT one week after diagnosis (when they return for treatment). Yet, this percentage was higher in women with single vaginal or rectal infection and in older women; this may affect treatment-choices. Disclosure: No significant relationships.